2020
DOI: 10.1186/s12992-020-00602-2
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric analysis of scientific publications on “sustainable development goals” with emphasis on “good health and well-being” goal (2015–2019)

Abstract: Background Global progress in the United Nations’ Sustainable Development Goals (SDGs) requires significant national and international research efforts and collaboration. The current study aimed to provide policymakers, academics, and researchers with a snapshot of global SDGs-related research activity. Method This was a cross-sectional descriptive bibliometric study. SciVerse Scopus was used to retrieve SDGs-related research publications for the period from 2015 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(73 citation statements)
references
References 42 publications
6
63
1
3
Order By: Relevance
“…This is not a surprise since this goal has a central role in the achievement of sustainable development (Pettigrew et al, 2015), and Biomedical Research is one of the largest research areas covered in Web of Science (Mongeon and Paul-Hus, 2016). In any case, our results are in agreement with (Körfgen et al, 2018;Sweileh, 2020), and as pointed out by previous studies, SDG3 "Good Health" was found to have a higher share of synergies with other SDGs in most countries (Pradhan et al, 2017). The MDGs, experience has shown that without improvements in health systems performance, progress on the goals was both limited and potentially unsustainable (Seidman, 2017).…”
Section: What Are the Specific Mandsdgs Research Topics That Have Beensupporting
confidence: 83%
See 1 more Smart Citation
“…This is not a surprise since this goal has a central role in the achievement of sustainable development (Pettigrew et al, 2015), and Biomedical Research is one of the largest research areas covered in Web of Science (Mongeon and Paul-Hus, 2016). In any case, our results are in agreement with (Körfgen et al, 2018;Sweileh, 2020), and as pointed out by previous studies, SDG3 "Good Health" was found to have a higher share of synergies with other SDGs in most countries (Pradhan et al, 2017). The MDGs, experience has shown that without improvements in health systems performance, progress on the goals was both limited and potentially unsustainable (Seidman, 2017).…”
Section: What Are the Specific Mandsdgs Research Topics That Have Beensupporting
confidence: 83%
“…The proposal of the different SDGs in 2005 together with Agenda 2030 has led to the creation of a path of collective national and international awareness toward sustainability. One of the main features of SDGs is their increasing relevance not only for policy makers, who are encouraging sustainability-oriented policies, but also for the scientific community as a whole (Kajikawa et al, 2007;Sweileh, 2020). This study presents an empirical scientometric analysis of M&SDGs research, and the role of HEIs in its development.…”
Section: Discussionmentioning
confidence: 99%
“… Bemke-Świtilnik et al (2020) examined collaboration trends in sustainable mining, and their results show increases in both the number of co-authored publications and in the average number of co-authors per article. At the country level, Sweileh (2020) found increased co-authored publications across all SDGs, though this varied by geographic region.…”
Section: Introductionmentioning
confidence: 93%
“…Other SDGs that dominated the overall retrieved literature included: SDGs of poverty (SDG 1), health (SDG 3), responsible consumption and production (SDG 12), climate action (SDG 12), sustainable cities and communities (SDG 11), and life on land (SDG 15). Meschede (2020) , like Sweileh (2020) , found that SDG 3 (“good health and well-being”) is prominent in SDG research, in an analysis of Scopus and Web of Science data that also identified major publishers and focal SDGs of the research by country of origin. Bautista-Puig and Mauleón (2019) analyzed documents about MDGs and SDGs to estimate research growth on these topics and create an ontology of key terms appearing in the literature.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation